Forty years of peritoneal dialysis Listeria peritonitis: Case and review. Issue 3 (May 2021) - Mat, Olivier; Gankam, Fabrice; Goubella, Ahmed; Colombie, Vincent; Blecic, Serge; Mat, Quentin; Philippart, Patrick
Infections with Listeria monocytogenes (LM) are very uncommon and severe especially in immunocompromised people. We report a continuous cycling peritoneal dialysis (CCPD) patient who presented initially disseminated listeriosis with peritonitis. He was successfully treated with intraperitoneal and intravenous ampicillin but died unfortunately from a cardiorespiratory arrest due to food inhalation. It is the 20th case of such peritonitis mentioned among PD patients and the first reported in Belgium. This case illustrates the importance of a systematic approach to get quick diagnosis and effective antibiotic readjustment. Empiric therapy is not effective on Listeria which is naturally resistant to cephalosporins and poorly sensitive to vancomycin. Ampicillin is the first-line antibiotic. In case of penicillin allergy, trimethoprim–sulfamethoxazole or erythromycin can be used successfully. Identification of LM serotype has a prognostic value. PD educative programmes should recommend to avoid unpasteurized dairy products to prevent listeriosis.